2021
DOI: 10.4103/ajns.ajns_520_20
|View full text |Cite
|
Sign up to set email alerts
|

Can apparent diffusion coefficient predict the grade, genotype, or proliferation index of oligodendrogliomas

Abstract: Background: Genetic subsets of oligodendrogliomas (OD) have distinct chromosomal and biophysical profiles. Pretherapeutic tumor grade and genotype analysis is a challenging aspect of management, with 1p/19q codeletion status and grade of oligodendroglioma among the most important considerations for clinical decision making. Methodology: Seventy-three patients with histopathological diagnosis of oligodendroglioma were selected, and their preoperative 1.5T magnetic resonance imaging (MRI) scans were reviewed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…To further contextualize the findings, this study emphasizes the importance of considering existing literature. Previous studies have demonstrated a correlation between irregular tumor contours and specific genetic signatures in a cohort of glioblastomas, aligning with the current observations and suggesting potential generalizability across different glioma subtypes [ 22 - 24 ]. Additionally, a study that investigated the association between radiological features and molecular subtypes of gliomas provided further evidence of the relevance of tumor morphology in predicting genetic alterations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…To further contextualize the findings, this study emphasizes the importance of considering existing literature. Previous studies have demonstrated a correlation between irregular tumor contours and specific genetic signatures in a cohort of glioblastomas, aligning with the current observations and suggesting potential generalizability across different glioma subtypes [ 22 - 24 ]. Additionally, a study that investigated the association between radiological features and molecular subtypes of gliomas provided further evidence of the relevance of tumor morphology in predicting genetic alterations.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have explored the synergistic role of radiogenomics, emphasizing the need for a holistic understanding of tumor biology [ 25 , 26 ]. Our findings contribute to this growing body of evidence, reinforcing the notion that radiological features, specifically tumor contours, can serve as valuable indicators of genetic alterations in gliomas [ 22 - 24 ]. Moreover, the link between tumor morphology and genetic characteristics has implications for prognosis and treatment response, demonstrating that certain genetic alterations, including 1p/19q co-deletion, are associated with an improved response to specific therapies in glioma patients.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations